Psychological Problems Of Adolescents: Their Impact On Personal Development In The Modern Social Environment (Theoretical–Conceptual Analysis) (Zien Journal of Social Sciences and Humanities, 2026)
This article provides a theoretical analysis of the essence of psychological problems encountered during adolescence, their causes, and their impact on personal development. Adolescence is one of the most complex and contradictory stages of human psychological development, during which the individual’s selfconcept, attitudes toward social roles, emotional stability, and behavioral patterns are formed. The modern information environment, the influence of social networks, the transformation of family relationships, and changes in the education system contribute to the intensification of such problems among adolescents as stress, internal conflicts, aggression, social isolation, and low self-esteem. The article reveals the interconnection of these problems with psychological, social, and cultural factors and substantiates conceptual approaches aimed at overcoming them